The common pattern of postmortem changes on whole body CT scans. (March 2016) - Klein, W.M.; Kunz, T.; Hermans, K.; Bayat, A.R.; Koopmanschap, D.H.J.L.M.
Abstract: The postmortem changes on postmortem computed tomography (PMCT) seem to have a regular pattern over time. Studying these changes could lead to a better understanding of postmortem physiology and to differentiate between normal and pathological aspects. We studied the patterns and aspects of the postmortem changes and made correlations to the postmortem interval (PMI). Five deceased bodies (4M, 1F; mean age 79 years; 2 cancer, 3 unknown cause of death) that were donated to science underwent total body PMCT scanning every hour, starting 6–10 h and up to 36 h after death. The bodies stayed on the scanner table during the whole scanning period, in supine position without moving. We measured Hounsfield units (HU) of the cerebrospinal fluid (CSF), vitreous humor (VH) and lungs. Volumes of lung, liver and bowel were calculated with semi-automated software. We made correlations to the PMI. We made timelapse movies to visualize the postmortem changes. We found increasing radiodensities of VH and CSF in correlation to the PMI. Pulmonary radiodensity and volume could show both increase or decrease over time. Liver volume decreased and bowel volume increased over time. The timelapse movies visualized these normal postmortem processes in the body. We conclude that postmortem changes on PMCT show partly a regular and partly diverging pattern between patients. The increasing radiodensity of CSF is correlated to PMI and might be helpful in estimating the time of death, however further study is needed. Highlights: Normal postmortem changes of the body are visible on PMCT. Radiodensity of CSF increase after death in correlation to the PMI. With increasing PMI, liver volume decreases and bowel volume increases. Lung volume gradually increases during the PMI due to both increasing edema and gas. Understanding changes on PMCT will lead to better diagnosis of pathologic processes.